2015
DOI: 10.1016/j.gie.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

EUS is superior for detection of pancreatic lesions compared with standard imaging in patients with multiple endocrine neoplasia type 1

Abstract: NTR1668.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
1
46
2
7
Order By: Relevance
“…We therefore stress the importance of a strict radiological follow-up for these lesions especially in patients managed conservatively. In this setting, EUS should be recommended for patients with usually long follow-up periods, due to its higher sensitivity and the lack of ionizing radiation [23]. The other advantage of EUS is to perform FNA for excluding from an active surveillance protocol those patients with higher-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore stress the importance of a strict radiological follow-up for these lesions especially in patients managed conservatively. In this setting, EUS should be recommended for patients with usually long follow-up periods, due to its higher sensitivity and the lack of ionizing radiation [23]. The other advantage of EUS is to perform FNA for excluding from an active surveillance protocol those patients with higher-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…With the optimization of the materials and techniques, EUS is progressively assuming the prominent position as first choice imaging procedure for the assessment of the pancreas in MEN-1 patients, being superior to CT, MRI, and somatostatin receptor scintigraphy [21, 22]. In such patient population, somatostatin receptor scintigraphy is considered being the most reliable method for the detection of metastatic disease [4].…”
Section: Discussionmentioning
confidence: 99%
“…It was developed as somatostatin receptor scintigraphy with 111 In-pentetreotide (SRS) in the 1990s and presented the standard imaging for GEP-NENs for more than two decades in most countries. The technique is based on the fact that GEP-NENs express somatostatin receptors (Shi et al 1998, van Essen et al 2013, especially the subtypes sst2 and sst5, which allow to visualize these tumors with radiolabeled somatostatin analogs. Several studies in the past have shown that the SRS scintigraphy is a useful imaging modality to detect pNEN and is even more sensitive than cross-sectional imaging (Gibril et al 1996, Langer et al 2004, Sundin 2012, van Essen et al 2013.…”
Section: :10mentioning
confidence: 99%
“…Compared to the general Dutch population, the breast cancer was diagnosed about 12 years earlier (Dreijerink et al 2014). The same group performed a cross-sectional case-control study using the Dutch MEN1 cohort (van Leeuwaarde et al 2017). In 138 MEN1 female patients, a questionnaire regarding breast cancer was carried out.…”
Section: Breast Cancermentioning
confidence: 99%